Laboratory manual on wood properties / Junaiza Ahmad Zaki ... [et al.] - Ahmad Zaki, Junaiza; Wan Abdul Rahman, Wan Mohd Nazri; Shafie, Amran; Abdul Jalil, Ainul Munirah; Mohd Yunus, Nor Yuziah (UiTM Press, 2019)
LABORATORY MAIS/UAL OF WOOD PROPERTIES is designed for used by pre-diploma, diploma and degree students. The narrative section of the manual can be used as reference manual for research and development purpose by post-graduate and others who are interested to test the various properties of bio-based material. The knowledge captured in the manual provides the testing technique based on or modified to follow closely Technical Association of the Pulp and Paper Industry (TAPPI) protocols. The tests covered in this manual can be separated to the physical, chemical and mechanical test on bio-based material. The tests include (i) physical - moisture content, density and specific gravity also shrinkage and swelling; (ii) chemical - extractives content, holocellulose, alpha-cellulose, lignin and ash content, and (iii) mechanical - bending. The manual provides narrative and pictorial guide deemed necessary for understanding these basic testing requirements of bio-based materials. The combination of physical, chemical and mechanical properties would enhance the understanding of bio-based as material for usage in laboratory exercises (quality) and research and development as well as production control.